Accounting for business : fundamental principles and practice - Marley, Stephen (Longman Cheshire, 1994)
This textbook contains 13 units: Unit 1-An introduction to the study of accounting; Unit 2-The accounting equation; Unit 3-The accounting system; Unit 4-Recording cash transactions; Unit 5-Control over cash; Unit 6-Recording other transactions; Unit 7-Recording credit transactions; Unit 8-Control of credit transactions; Unit 9-End of period adjustments; Unit 10-Preparation of end of year reports; Unit 11-Recording and control of property, plant and equipment; Unit 12-Recording and control of payroll; Unit 13-The complete accounting process